Pernicious Anemia with Autoimmune Hemolytic Anemia: A Case Report and Literature Review - Sri Lakshmi Hyndavi Yeruva; Raj Pal Manchandani; Patricia Oneal (Case Reports in Hematology)
Pernicious anemia is a common cause of vitamin B12 deficiency. Here, we discuss a case of a young woman who presented with severe anemia along with a history of iron deficiency anemia. After a review of her clinical presentation and laboratory data, we identified an autoimmune hemolytic anemia and a concomitant pernicious anemia. The concurrence of both these hematological diagnoses in a patient is rare.